Music for a King George Herbert's Style and the Metrical Psalms - Freer, Coburn (Johns Hopkins University Press, 2020)
Originally published in 1972. Music for a King tries to study the affinities in form and matter between the versified translation of the Psalms and George Herbert's lyrics. Coburn Freer reads Herbert's poetry by way of the metrical psalms that precede it, proposing a reading that could be applied to more poems than are discussed here. Rather than multiply examples needlessly, this book stresses a few central poems as models or representatives. This reading of Herbert recognizes the historical dimension of his poems, but the author does not make that dimension the only significant one in the determination of poetic meaning or value.